Kedudukan Pegawai Tidak Tetap (Tenaga Honorer) Setelah Berlakunya Undang-Undang Nomor 5 Tahun 2014 - I Kadek Suryantara Bagus Wiranata; Ida Ayu Putu Widiati; .PT.GD. Seputra (Fakultas Hukum Universitas Warmadewa, 2020)
The enactment of Law Number 5 of 2014 concerning State Civil Apparatuses influences the position of temporary employees or honorary staff. The problem in this paper is how to regulate the legal status of non-permanent employees after the enactment of Law Number 5 of 2014 concerning State Civil Apparatuses, as well as concerning legal protection of Temporary Employees (honorary workers) after the enactment of Law Number 5 of 2014 concerning Apparatus State Civil. To solve this problem, research is conducted using normative methods, sources of primary and secondary legal materials, methods of gathering legal materials using the recording of laws and other literature, and analyzing legal materials using legal arguments. The results of this study that the legal protection of Non-permanent Employees (honorary workers) after the enactment of Law Number 5 of 2014 concerning State Civil Apparatus is in Law Number 5 of 2014 concerning State Civil Apparatuses no longer found the term Permanent Employees or honorary employee. But when viewed from the classification of Civil Servants (PNS) and Government Employes with Work Agreements (PPPK). Based on Law Number 5 of 2014 concerning State Civil Apparatus Article 8 Government Employees with Work Agreements (PPPK) are located as one of the elements of the state apparatus. Legal protection for Non-permanent Employees (temporary workers) after the enactment of Law Number 5 of 2014 concerning State Civil Apparatus is protection in the form of old age insurance; health insurance; accident insurance; life insurance; and legal assistance. Protection in the form of old age insurance, health insurance, work accident insurance, and death insurance is carried out in accordance with the national social security system.